Такие, какие есть: [роман] / Сьюзен Одо ; [пер. с англ. О. Г. Качковского] - Одо Сьюзен (Страсть, 2003)
Экземпляры: ф.3 (2003) / Инвентарный номер: 45584 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: О-44 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44